Algorithms in Judicial Environments – the Importance of Identifying Relevant Judicial Decision-Making Stage - Murauskas, Donatas (Teisė, 2020)
The paper examines the application of Artificial Intelligence systems in the judicial environments. It provides an outline of a typology of different algorithms applicable in judicial environments depending on judicial decision-making stage. This is a positive analysis which aims at identifying relevant algorithms in every judicial decision-making stage, be it assessing the facts, indicating the applicable law or deciding.